Morphological dimorphism varies across the endemic Xantus’ hummingbird (Hylocharis xantusii) genetic populations in the Baja California Peninsula - González-Rubio Sanvicente, Cristina; García-de León, Francisco J.; Rodríguez-Estrella, Ricardo (Instituto de Ecología, A.C., 2018)
Morphological dimorphism traits play an important role in our understanding of species evolution. In birds, sexual dimorphism occurs in a number of characteristics, such as body and shape size, wing and bill morphology. Hylocharis xantusii is the only hummingbird species endemic to the Baja California Peninsula, Mexico that has adapted to xeric conditions, associated to oases regions, and displays a sexual dimorphism on color pattern. We quantified morphological variation between males and females to determine whether morphological traits have a significant contribution to sexual dimorphism, and we analyzed if differences in morphological patterns among genetic populations of Xantus’ hummingbird existed. A morphological dimorphism was found in four of six traits analyzed, males were bigger in size (total length) with larger wings (wing chord and tail length) and wider bills (bill width). Differences in morphological traits of genetic populations were found. Individuals of southern population were in average smaller than central and northern populations while individuals from central populations had larger bills and wing chords. Northern populations had longer tails and wider bills. The results indicated that populations and sex are independent to morphological differences in Xantus’ hummingbird. The best fitted GLM shows that the altitude and oasis location related to the genetic population correctly explains the differences in tail, wing chord and bill width traits of hummingbirds along the Baja California Peninsula. We suggest that local conditions related to environmental heterogeneity and oases distribution are promoting levels of morphological differentiation. Genetic populations were already known to be result of their evolutionary history, of the phylogeographic pattern. Sexual dimorphism on morphological traits observed in H. xantusii is related in first place to ecological differences among oases, and second, related to mating and social behavior.